Social inclusion : Dutch perspectives : factors for success and failure. - Kröber, Hans R.Th., ....-; Steenbrink, Annelies, ....-; van Dongen, Hans J., ....- (Amsterdam : Boom Nelissen, 2011)
Inclusion is an important component of quality of life. It is linked to issues such as participation in society, relationships, social networks and civil society. Viewed from this perspective, the social position of people with an intellectual disability in Europe in general and in the Netherlands in particular, still leaves much to be desired. Often segregation and marginalization still exist. Social Inclusion focuses on the factors for success and failure that come into play when designing inclusion processes. The book examines the role of health care organizations and their contributions to inclusion. From the perspective of the health care organization, the following issues are explored: To what extent has the history of health care been obstructive for inclusion? Which roles do government, advocates and stakeholders play? Which roles are played by organizational features, the employees and those with an intellectual disability who are supported by a health care organization? Which implementation strategy would be the most appropriate when designing changes? The book shows that important lessons can be learned from Dutch health care. It provides valuable insights resulting from the research that lies at the basis of this publication.
Keywords: Gehandicaptenzorg; Inclusie